IMPACT OF HERBAL DRUGS ON BUYER’S PURCHASE OVERALL SATISFACTION IN MALAYSIA - Hamid, Junainah Abd; AK, Sairah (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the relation between service quality, perceived safety as independent variable and overall customer satisfaction as dependent variables that pertains multiple aspects in the context of herbal medicine among women in Malaysian. The investigation will elucidate the association between independent and dependent variables. The conclusion is that there is positive association between service quality, perceived safety (independent variables) and overall customer satisfaction (dependent variable). The questionaries’ response rate stands at 81%. Furthermore all the two hypotheses are accepted. This investigation will provide the new insights to herbal manufactures, retailers, educational institutions.